Analisis Pandangan Masyarakat terhadap Makam Sido Ing Rejek di Desa Sakatiga Kecamatan Indralaya Kabupaten Ogan Ilir Provinsi Sumatera Selatan Tahun 2010-2023 - Maharani, Sherlya; Yusuf, Syafruddin (Riwayat: Educational Journal of History and Humanities, 2025)
This study uses a qualitative approach with in-depth interview methods, observation, and documentation studies. The results of the study indicate that in general, the condition of the tomb complex is still well maintained even though there is minor damage due to natural factors and lack of intensive care. The Sakatiga Village community has a positive perception of the existence of the tomb, which is considered an important historical and spiritual site. The tradition of pilgrimage and other religious activities are still actively carried out, strengthening social relations and the cultural identity of the local community. This study also found that the tomb has an important role in the social, cultural, and spiritual life of the community, and has the potential to become a cultural tourism object that can increase awareness of the preservation of local cultural heritage. Therefore, the preservation of the tomb and education for the younger generation are very important to ensure the sustainability of this cultural heritage in the future.